The Parallel Imports of Invention Patents in Pharmaceutical Products (International Journal of Scientific Research and Management (IJSRM), 2022)
This research was carried out with the aim of knowing the nature of parallel imports, regulations in optimizing parallel imports of pharmaceutical patent products and strategies for using parallel imports in pharmaceutical patent product inventions in Indonesia. This research uses a normative type of research by utilizing a legal research approach and a conceptual approach. The results of this study, namely: 1) Parallel import is an activity of importing patent protected inventions without third party permission to the inventor/patent holder so that the patent holder cannot enjoy the incentives for the exploration process by a third party. This activity is carried out because it is crucial and fundamental in nature, namely the interests of health and is related to human life. This activity is to ensure a reasonable price and fulfill a sense of justice for essential pharmaceutical inventions that are very much needed by humans and can cure diseases. The implication is the lack of a sense of justice for the inventor/patent holder and the inventor/patent holder cannot enjoy the maximum economic benefits and exclusive rights over the third party invention exploration process. However, there are exceptions to minimize losses for inventors/patent holders, namely the doctrine of national exhaustion (earning royalties and economic benefits from the first sale) which upholds Article 19 of Law no. 13 of 2016. 2) importers are required to fulfill administrative requirements such as distribution permits, pharmaceutical industry permits from abroad and SKI Border or Post Border. Regulation of parallel import pharmaceutical inventions is regulated in the TRIPs Agreement, Law No. 13 of 2016, Law no. 36 of 2009, Law no. 17 of 2006, Regulation of the Minister of Trade of the Republic of Indonesia Number 17 of 2021, Law of the Republic of Indonesia Number 20 of 2014, BPOM Regulation Number 15 of 2020 and PerKa BPOMRI Number 24 of 2017. 3). Parallel import strategy for patent pharmaceutical inventions with an obligation to importers to complete administrative requirements to prevent misuse of parallel imports, and in accordance with the provisions of Article 167 letter (a) which states a price determination in order to obtain cheaper prices in the international market and reduce competition. healthy so that consumers can get fair prices and create a sense of justice, adhere to the national doctrine of exhaustion which pays attention to the interests of inventors, and imports in reasonable quantities to foster a sense of justice between inventors and importers.